PET-SAÚDE REDES DE ATENÇÃO: CONCEPÇÃO PEDAGÓGICA E METODOLÓGICA - Fontenele Coutinho, Susan Karolliny Silva; do Nascimento, Antonio Ciro Neves; Melo Moreira, Ana Ester Maria; Galvão Araújo, Tássya Bruna (SANARE - Revista de Políticas Públicas, 2015)
-